A STUDY OF CLINCOETIOLOGICAL PROFILE OF PATIENTS WITH PLEURAL EFFUSION: A CROSS-SECTIONAL STUDY - ARYA, SHASHIKANT; GUPTA, ARCHANA; NANDURKAR, PAWAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of this study was to determine the clinical profile, etiology in patients presenting with plural effusion and correlation between etiology, clinical, and radiological findings. Methods: It was a cross-sectional study carried out at the GRMC JAH Department of Medicine, Gwalior, from to July 2013 to October 2014 after getting the permission from the Institutional Ethical Committee. Inclusion criteria were all 100 patients above 14 years of age with clinical and radiological evidence of plural effusion. Patients with history of trauma chest and thoracocentesis were excluded from the study. The demographic variables were gender, age in years, sex, and address. The research variables were breathlessness, fever, cough, chest pain, generalized edema, abdominal pain, hemoptysis, and cause of pleural effusion. Investigations such as complete blood count, retained blood syndrome, renal function test, serum albumin, chest X-ray, pleural fluid analysis, ultrasonography chest and abdomen, echocardiogram, upper gastrointestinal endoscopy, blood culture, fine-needle aspiration cytology, and computed tomography scan. There were eight age groups between below 21 years and above 81 years. Nominal data were analyzed for frequency and (%) and the numeric data were analyzed by Chi-square test p-value. Results: In the present study, maximum cases (66%) presented with exudative type of pleural effusion. Of these 43 cases (65.15%) had tuberculosis, 5 cases (7.5%) had malignancy and 4 cases (6.06%) had pneumonia. About 34% cases presented with transudative type of pleural effusion. Of these 10 cases (29.41%) had hepatic involvement, and 8 cases (23.52%) had congestive cardiac failure. Acute febrile illness 9 (9%), nephrotic syndrome 4 (16%), renal failure 5 (5%), hypoalbuminemea 5 (5%), pancreatitis (1%), and adult respiratory distress syndrome (1%) were other causes of pleural effusion in this study.